The effect of perceived ease of use on continuance intention through perceived usefulness and trust - Dading Jatimoyo (International Journal of Research In Business and Social Science, 2021)
E-commerce is one of the industries that are able to grow in the middle of the crisis because of the COVID-19 pandemic. This research aims to investigate the factors that influence the continuance intention of online shopping services in the scope of e-commerce. This research uses perceived ease of use as an independent variable that affects the intention with perceived usefulness and trust as mediating variables. This research is categorized as explanatory research. Respondents in this study are Klikindomaret users and the determination of the number of samples in this study using purposive sampling technique with a total sample of 170 respondents. The data collection method used a questionnaire and the data was analyzed using PLS-SEM. The findings of this study indicate that perceived ease of use, perceived usefulness, and trust have a significant effect on continuance intention. Perceived usefulness and trust also play a role in mediating the relationship between perceived ease of use and continuance intention.